Analysis of Biopellets from a Mixture of Coffee Grounds and Sawdust as an Alternative Energy Source: Analisis Biopelet Dari Campuran Ampas Kopi dan Serbuk Gergaji Sebagai Sumber Energi Alternatif - Muhamad Farad Sutarya; Damora Rhakasywi; Fahrudin Fahrudin (Academia Open, 2025)
Background: Indonesia’s growing energy demand and dependence on fossil fuels necessitate renewable alternatives such as biomass-based biopellets. Specific Background: Coffee grounds and sawdust are abundant organic wastes with complementary thermal and mechanical properties suitable for pelletization. Knowledge Gap: However, limited studies have clarified how varying proportions of these materials influence biopellet quality relative to SNI 8021:2020 standards. Aims: This study evaluates the effects of four ratios of coffee grounds–sawdust mixtures (80:20, 70:30, 60:40, 50:50) on physical and proximate characteristics of biopellets. Results: One-way ANOVA and Tukey HSD (p < 0.05) showed significant differences across all parameters. Formulations A and B produced the highest calorific values (4674–4689 cal/g) meeting SNI requirements, while B achieved the highest density (560.34 kg/m³). Moisture and ash contents also met standards; however, density and fixed carbon fell below SNI thresholds due to the absence of torrefaction. Novelty: This study demonstrates that optimizing coffee grounds–sawdust mixtures alone cannot meet all quality indicators without thermal pretreatment. Implications: Incorporating torrefaction and enhanced pressing conditions is essential to improve energy density and combustion stability, supporting the development of high-quality waste-based biofuel in Indonesia. Highlights: The optimal calorific value is achieved with higher proportions of coffee grounds (80:20 and 70:30). Density and fixed carbon remain below SNI standards due to the absence of torrefaction. Thermal pretreatment is essential to improve combustion stability and overall pellet quality. Keywords: Biopellet, Coffee Grounds, Sawdust, Biomass Energy, Torrefaction